Studi Terhadap Kinerja Pegawai Pusdik Binmas Lemdiklat Polri Banyubiru - Hana Riskiani; Nanda Adhi Purusa; Sih Darmi Astuti; Hertiana Ikasari (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to examine the influence of inclusive work culture, work environment, and work-life balance on employee performance at Pusdik Binmas Lemdiklat Polri Banyubiru. The approach used is quantitative with a survey method through a questionnaire distributed to 100 respondents. The results of the analysis show that the three variables have a positive and significant relationship to employee performance. Inclusive work culture was found to be the most dominant factor in improving performance and productivity, followed by the role of a conducive work environment and the importance of work-life balance. The results of this study indicate that improving employee performance requires support from an inclusive work culture, good relationships between employees, and proportional work time management.